Volatile organic compounds released by Rumex confertus following Hypera rumicis herbivory and weevil responses to volatiles. (22nd May 2015) - Piesik, D.; Wenda‐Piesik, A.; Krasińska, A.; Wrzesińska, D.; Delaney, K. J.
Abstract: We report in this study large induction of volatile organic compounds (VOCs) from a single inflorescence of mossy sorrel ( Rumex confertus Willd., Polygonaceae ), by herbivory of the weevil ( Hypera rumicis L., Coleoptera : Curculionidae ). VOCs blend induced by the weevil herbivory included 1 green leaf volatiles (GLVs) ((Z)‐3‐hexen‐1‐yl acetate), five terpenes ((Z)‐ β ‐ocimene, linalool, geranyl acetate, β ‐caryophyllene and (E)‐ β ‐farnesene), three esters (benzyl acetate, methyl salicylate and methyl anthranilate) and one aromatic heterocyclic organic compound (indole). Uninjured plants produced only detectable amounts of VOCs. A Y‐tube experiment revealed that both females and males of H. rumicis were not attracted to any of tested concentrations (1, 5, 25, 125 ng/min). Also both females and males were significantly repelled by the highest concentrations (25 and 125 ng/min). Additionally, concentration of 5 ng/min proved to be repellent for females of H. rumicis .